New findings on urinary prostate cancer metabolome through combined GC–MS and 1H NMR analytical platforms - Lima, Ana Rita (2021)
The inherent sensitivity of metabolomics allows the detection of subtle alterations in biological pathways, making it a powerful tool to study biomarkers and the mechanisms that underlie cancer.